Chloranthus coccineus (Chloranthaceae), a new species from Hubei, China - He, Li-Hong; Zhao, Xin-Lei; Yu, Jing; Zhang, Zhao (Phytotaxa, 2022)
Chloranthus coccineus, a new species discovered in Hubei Province, China, is illustrated and described. It is shown to be similar with C. fortunei by detailed morphological comparison and chromosome number count. However, they are easily distinguished by the lengths of the peduncles, the colors of leaf veins when dry and the colors of stamen connectives. Karyotype also lends strong support for the validity as a new species. Moreover, the phylogenetic analyses based on nuclear ITS2 and plastid trnL-F data from seven taxa of Chloranthus showed that the putative new species is closest to C. fortunei but they are reciprocally monophyletic to each other for the sampled individuals from different populations. In conclusion, morphological, cytological and molecular evidence supports that C. coccineus is a new species.